Comparing Mangrove Diversity and Soil Composition Along The Coast of Barangay Pamosaingan, Socorro, Surigao del Norte, Philippines - Baranggan, Jhondel P.; Sarmen, Aldwin Y.; Eviota, Manny P.; Cawaling, Archie D. (Indonesian Journal of Environment and Sustainability Issues, 2025)
Mangrove ecosystems provide critical ecological services and are highly sensitive to environmental variables, particularly soil characteristics. This study explores the relationship between soil composition and mangrove species diversity along the coast of Barangay Pamosaingan, Socorro, Surigao del Norte, Philippines. A stratified random sampling design was applied, establishing twenty 10 m × 10 m quadrats across three ecological zones based on tidal influence. Mangrove species within each quadrat were identified and recorded, while soil samples were collected at a 30 cm depth for granulometric analysis using a series of standard sieves. Species diversity was assessed using Simpson’s Diversity Index, and relationships between soil texture and diversity were evaluated through Pearson correlation analysis. The study identified eight mangrove species from four families, with Rhizophora apiculata emerging as the dominant species across the majority of quadrats. Sieve analysis revealed that fine sand constituted the majority of the substrate, with 77% of soil particles passing through the No. 10 sieve. A strong positive correlation (r = 0.964) was found between fine sand content and species diversity. These findings suggest that fine-grained sediments offer favorable conditions for mangrove growth and species richness. The results provide a basis for targeted conservation strategies, particularly in regions with similar coastal soil characteristics, and underscore the ecological relevance of substrate type in sustaining mangrove biodiversity.